Sacramental Theology: Theory and Practice from Multiple Perspectives: Theory and Practice from Multiple Perspectives - Morrill, Bruce (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Throughout the second half of the twentieth century, sacramental theology has evolved as a discipline advancing comprehensive theories of sacraments and sacramentality as integral to the Christian faith while also studying the history and theology of the particular rites. Now, in the twenty-first century, the need for attention to the actual performance and specific social settings of sacramental worship has become well established. This makes the work of sacramental theology necessarily engaged with multiple, cross-disciplinary theories attentive to particular contexts, whether local, national, or global. Still, the divine human encounter at the heart of Christian symbol and ritual likewise beckons to philosophical-theological reflection. The essays in this volume begin with profound philosophical perspectives on the personal and communal sacramental experience, expanding from traditional cosmology to evolutionary and chaos theories of our planetary existence, continuing with shifts, especially among youth, to interreligious and non-institutional perspectives, consideration of change in popular notions of guilt, and social-ethical issues in relation to liturgical theology and practice, so as finally to return to fundamental theological reflection on human sacramentality and divine revelation.